Medidas de duração de consoantes oclusivas como vestígios de fala em análise acústico-instrumental forense de amostras com e sem uso de disfarce - Carneiro, Denise de Oliveira (2016)
Authorship attribution of speech, from environmental recordings and telephone interceptions, which can be evidence of crimes related to drug dealing, racketeering, kidnapping, sexual abuse, pedophilia, and corruption, may present difficulties to experts in obtaining acoustic measures. One of these difficulties may be the use of disguise. With the possibility of being recorded, voice disguise has become common among crime perpetrators. When a voice is recorded, it can be an evidence after speaker comparison examination (SCE), which adopts methodologies to determine whether two speech samples have been produced by the same speaker. SCE can be perceptual, acoustic-instrumental and through automatic recognition. Although automatic recognition technologies have already been developed, analyses without human interference do not have enough support, both for poor signal quality or for lack of speech samples. Therefore, research that is anchored in other analysis methods are essential. Acoustic-instrumental analyses use computational tools for quantitative and qualitative evaluation of speech, and biomedical engineering enables the development of technologies and instrumentation for speech signal analyses. In search of an acoustic parameter that is robust in disguise analyses, this research used segment phase measurements, which have been little explored in SCE. Brazilian Portuguese voiceless stops [p, t, k] are produced in three distinct phases: occlusion phase, release phase and formant transition. The first two phases have acoustic correlates that are visually distinct in the oscillogram: relative silence and aperiodic wave production. In this research, the speech of 20 subjects were instrumentally analyzed, 10 males and 10 females, aged between 25 and 55 years, while reading, with and without the use of disguise, a text that simulated a criminal situation. Occlusion and release duration of the voiceless stop consonants were measured and it was found that the phonological context influences the production time. Different measures were found between the first and the second reading with disguised voice, indicating that the speaker had difficulty in maintaining the phonation setting, and that, although there were differences between the measures in speech with and without disguise, the correlation between them was strong. Occlusion time appeared to be less influenced by the use of disguise for the syllables [pi, pu, te, tɛ], while the release time showed greater susceptibility, except for [pi, te]. The results allow that some of the segments analyzed be considered vestiges of authorship within a body of evidence.